A new bench-scale methodology for evaluating the flammability of live forest fuels. (March 2013) - Madrigal, Javier; Hernando, Carmen; Guijarro, Mercedes
The present study proposes a new method in order to evaluate the flammability of live plant parts at bench-scale. Flammability parameters were estimated by the use of a mass loss calorimeter, and fuel moisture content was evaluated by the use of moisture analyser. Forest fuels ( Pinus pinaster, Cistus laurifolius, Lavandula stoechas and Daphne gnidium ) were monitored under field conditions to detect the changes in the fuel moisture contents during the fire risk season. The combination of two different bench-scale devices (moisture analyser and mass loss calorimeter) guarantees fixed conditions for carrying out laboratory tests (constant bulk density and constant sample dry mass), thus resolving problems detected with other devices and methodologies.